Exploring functional fungi on organic matter decomposition of oil palm empty bunches as bio-resource in land remediation - Burhanuddin Rasyid; AMBO ALA; TUTIK KUSWINANTI; SUKRIMING SAPARENG (Society for Indonesian Biodiversity, 2020)
Abstract. Rasyid B, Ala A, Kuswinanti T, Sapareng S. 2020. Exploring functional fungi on organic matter decomposition of oil palm empty bunches as bio-resource in land remediation. Biodiversitas 21: 4247-4252. Organic matter of oil palm by-product has the potential to be applied for land remediation. The objective of this experiment was to explore functional fungi on the decomposition effectivity of oil palm empty bunches. Samples were collected from oil palm plantation fields and oil palm factory. Isolated fungi from decomposed material (trunks and rod) were Penicillium sp., Pleurotus sp., Fusarium sp., Chrysosporium sp., and Aspergillus sp. Fungi in the empty fruit branches were identified as Absidia sp., Tremella sp., and Trichoderma sp., Phytophthora sp., Ulocladium sp., and Chaetomium sp. Within all collected fungal isolates, Pleurotus sp., Trichoderma sp., and Tremella sp. were selected as functional fungi based on the results of the highest lignocellulolytic ability (50-75%). The degradation rate of organic matter of each functional fungi was observed as Trichoderma sp. (24.0%), Tremella sp. (20.0%), and Pleurotus sp. (16.0%). Change of C/N ratio as a result of decomposition showed significant difference compared to control with 22.09 by Trichoderma sp., 24.26 by Pleurotus sp., 26.68 by Tremella sp. and 36.58 in control. This study could be concluded that exploring functional fungi can potentially be applied in the decomposition of oil palm by-product effectively.